Neurodevelopmental and emotional-behavioral outcomes in late-preterm infants: an observational descriptive case study - Roberto Palumbi; Antonia Peschechera; Mariella Margari; Francesco Craig; Arcangelo Cristella; Maria Giuseppina Petruzzelli; Lucia Margari (BMC, 2018)
Abstract Background Over the last decade, several studies investigated the outcomes in children born very preterm. Only recently there has been an increasing interest in the late preterm infants (born between 34 + 0 and 36 + 6 weeks). This population is at high risk of morbidity and mortality in the first years of life. Other studies reported that they are also at risk of long-term developmental problem. Therefore, the aim of this study is to describe the neurodevelopmental and emotional-behavioral outcome in a sample of late preterm patients. Methods The study included late preterm children and adolescents who had neuropsychiatric and/or neurological symptoms. They underwent a general, neurocognitive and an emotional-behavioral assessment. Exclusion criteria included: patients affected by Central Nervous System congenital abnormalities, neurodegenerative diseases, genetic disorders, epilepsy, or in pharmacological treatment, or adopted children. A descriptive statistics analysis was performed to describe the sociodemographic and clinical characteristics of patients. Risk factors related to late preterm birth, prevalence of neurodevelopmental disorders, and cognitive functioning were recorded and analyzed. Results The sample included 68 LPI (45 males and 23 females) aged from 2 to 16.3 years (mean age 7,5 years), who were affected by one or more neurodevelopmental disorder, including Language Disorder, Attention Deficit Hyperactivity Disorder, Specific Learning Disorder, Developmental Coordination Disorder, Intellectual Disability and Autism Spectrum Disorder. Moreover, in 30.8% of patients, internalizing problems (affective and social skills problem) were detected. Conclusions Our results support the importance of a long-term surveillance of late preterm and the great need for more longitudinal large population studies in order to collect data on the neurodevelopmental outcomes of this population.